2022
DOI: 10.3389/fnut.2022.853332
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Dietary Inflammatory Index and S-Klotho Plasma Levels in Middle-Aged and Elderly People

Abstract: Background and AimsSoluble Klotho (S-Klotho) is a protein that has anti-aging properties. Dietary inflammation index (DII) is closely related to various age-related diseases. However, whether DII is related to S-Klotho plasma levels is still controversial. It was the goal of this study to examine the link between DII and S-Klotho in middle-aged and elderly people.MethodsBetween 2007 and 2016, five NHANES cycles were conducted, with 12,315 middle-aged and elderly (aged 40–79) participants having S-Klotho tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Although these dietary quality measures are not entirely consistent, previous studies have demonstrated similar associations between different dietary qualities and S-Klotho. For example, both Chi-Chen and our previous NHANES studies imply that an inflammatory diet may lower S-Klotho levels ( 28 , 29 ). Shou-En found a positive association between Mediterranean adherence diet score (MDS) and S-Klotho levels based on NHANES.…”
Section: Discussionmentioning
confidence: 83%
“…Although these dietary quality measures are not entirely consistent, previous studies have demonstrated similar associations between different dietary qualities and S-Klotho. For example, both Chi-Chen and our previous NHANES studies imply that an inflammatory diet may lower S-Klotho levels ( 28 , 29 ). Shou-En found a positive association between Mediterranean adherence diet score (MDS) and S-Klotho levels based on NHANES.…”
Section: Discussionmentioning
confidence: 83%
“…As it is widely acknowledged, there exists an anti-aging protein in plasma, soluble Klotho (S-Klotho). A research had indicated a negative association between S-Klotho and pro-inflammatory food patterns evaluated based on DII in people over 40 years old ( 26 ). Furthermore, these middle-aged and older people with high DII scores also had an increased likelihood of suffering from low HDL cholesterol, hyperglycemia, and metabolic syndrome ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Ma et al. found that chronic inflammation, caused by a pro-inflammatory diet pattern, can reduce serum klotho levels ( 37 ). Thus, as a characteristic of the obese state, the excessive proinflammatory products, mainly from adipose tissue, may in turn deplete the klotho protein in the serum, reducing its concentration.…”
Section: Discussionmentioning
confidence: 99%